Portability, an innovative property tax relief whose time hasn't come. Issue 2 (1st March 2015) - Guo, Hai (David); Frank, Howard A.
Abstract : The Florida electorate passed Amendment One on January 29th, 2008. The portability provision of this Amendment allows homestead owners to transfer the difference between assessed value and estimated market value of their current homestead property to their new property. Since passage, there has been limited and declining utilization of the portability provision. This paper explores whether the accrued tax savings due to the property assessment limit provide sufficient incentive for homesteaders to move by examining aggregated utilization of the portability provision among counties. Based on a panel regression using 67 counties from 2008 to 2012, our findings indicate the portability provision has had limited impact on Florida's depressed housing market and only a small number of well-educated and white homesteaders have availed themselves of this mechanism.